Changes in the mineral status in the organisms of young athletes within one-year training cycle - Krupskaja, T.; Loseva, L.; Pushkareva, M.; Tsivunchyk, O.; Anufrik, S.; Milasius, K.; Peèiukoniene, M. (Baltic Journal of Sport and Health Sciences, 2016)
Background. Concentration of trace elements in the hair allows to get an idea how they are taken by the organism over a long period of time and to study relative correlations with different genetic, dietary and environmental factors. Research aim was to identify changes in the macro- and microelement status for young athletes involved in different sports activities depending on the preparation period within one-year training cycle. Methods. A total of 78 young athletes aged 12-17 years, 32 of which were swimmers (group I), 17 - tennis players (group II) and 29 - Taekwondo athletes (group III) participated in the study. Biological material (hair samples), the volume of 0.1-0.15 g were taken for experimental studies in three periods of time: preparatory, competitive and transition period within a one-year training cycle. Hair samples were analyzed using the method of X-ray fluorescence (XRF) in order to detect multiple elements. For quantitative analysis, 8 chemical elements (sulfur, potassium, calcium, iron, copper, zinc, strontium and selenium) were determined in a single hair sample. Results and conclusion. A non-invasive method to determine mass fraction of the chemical elements (sulfur, potassium, calcium, iron, copper, zinc, lead, chlorine, bromine, strontium, selenium) in a hair sample is an informative method for assessing the physiological response of the body (young athletes) with physical activity at different stages of training. The statistical analysis of the obtained results revealed the dependence of the concentration of trace elements from a kind of sports activity and stage of preparation for young athletes.